The Role of Learning Media in Strengthening Civic Education Learning in Elementary Schools - Anisa Hasibuan, Putri; Nurhasanah, Khairyah (International Journal of Students Education, 2023)
This research examines how Civic Education is taught through digital learning resources. Inductive data analysis is one of the qualitative research methodologies used in this study. The purpose of this study is to determine the role of learning media in strengthening civic education learning in elementary schools.One of the ways learning media strengthens civic education is by helping learners become more independent, responsible, critical, and active citizens who can engage in politics, society, and government at all levels in an effective and efficient way. information in the era of globalization that is affordable by students' learning capacity, uses real learning, and is able to attract students' interest and attention and encourage critical thinking. Teachers can choose the most effective learning materials, whether they are still, audio or graphic, based on these qualities. If the projection media is still, graphic, or audio, the teacher can determine whether the projection media is still, graphic, or audio. After that, the teacher can use the media with the premise that all forms of media have advantages and disadvantages, that media should be used sparingly, and that media can engage students actively. Along with the results show that the role of media in learning ppkn is very important, an educator is guided to develop innovative learning media needed in the education system to improve and achieve citizenship competence, as well as to downstream the scientific progress of civic education and make it more adaptable to the changing needs of learning. which, in the era of digital learning media, can adapt to the demands and progress of education.